Facile Synthesis of Highly Fluorescent Free-Standing Films Comprising Graphitic Carbon Nitride (G-C3n4) Nanolayers - Singh, D (Royal Society of Chemistry, 2020)
Astounding graphitic carbon nitride (g-C3N4) nanostructures have attracted huge attention due to their unique electronic structures, suitable band gap, and thermal and chemical stability, and are insinuating as a promising candidate for photocatalytic and energy harvesting applications. The growth of a free-standing film is desirable for widespread electronic devices and electrochemical applications. Here, we present a facile approach to prepare free-standing films (15 mm × 10 mm × 0.5 mm) comprising g-C3N4 nanolayers by the pyrolysis of dicyandiamide (C2H4N4) utilizing the chemical vapor deposition (CVD) technique. The synthesis is done under low-pressure conditions of argon (∼3 Torr) and at a temperature of 600 °C. The as-synthesized g-C3N4 films are systematically studied for their structural/microstructural characterization using X-ray diffraction (XRD), scanning and transmission electron microscopy (SEM and TEM), X-ray photoelectron spectroscopy (XPS), Fourier-transform infrared spectroscopy (FTIR) and UV-visible spectroscopy techniques. The excitation-dependent photoluminescence (PL) spectra of the as-synthesized g-C3N4 film exhibited an intense, stable and broad emission peak in the visible region at ∼459 nm. The emission spectra of free-standing g-C3N4 films show a blue shift and band sharpening compared to that of the g-C3N4 powder. This journal is © The Royal Society of Chemistry and the Centre National de la Recherche Scientifique.